Improved curve tracing in images - Raghupathy, K.; Parks, T.W. (2004 IEEE International Conference on Acoustics, Speech, and Signal Processing, 2004)
This paper begins with a description of the curve tracing problem and compares it with curve extraction, a fundamentally different problem. Issues concerning curve tracing are addressed. We discuss a good curve tracing algorithm proposed by Carsten Steger and improve this method to suit the goals of curve tracing. Results show that the improved algorithm emulates human perception by using both global and local features.